(3efGgL GdHMK GdYdej aj eLGd GdeMGSHI (B/s - .(3GdOgQGhj, ceGd GdOjfs ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2002)
(3efGgL GdHMK GdYdej, GdGWGQ GdfXQj hhVY hUjGZI GdaQhV, CfhGY GdHMhK, GdJUeje GdJLQjHj ddHMK, bjGS GdeJZjQGJ, WQb JLejY GdHjGfGJ, GdeYGjfI GdGMUGFjI, GdGNJHGQGJ GdGMUGFjI ddaQhV , GJLGgGJ eYGUQI dJWhjQ GdHfGA GdacQj ddeMGSHI GdGOGQjI h eUOGbjI GdeYdheGJ GdeMGSHjI aj Xd GdJVNe h JhGRf Gdbhi Hjf GdeQGLY h GdTQcI h CKQg Ydi GSJbdGd GdeQGLY h OQGSI JMdjdjI dCKQ CSdhH hVY h eSJhi GdehGRfI GdJNWjWjI Ydi COGA GdeOjQjf h CNjQG OQGSI JLQjHjI ddGNJdGaGJ aj OQLI GdGaUGM GdeMGSHj Hjf GdTQcGJ GdchjJjI h CKQ JUfja GdhSGFd GdeGdjI GdMOjKI Ydi GdeMJhi GdeYdheGJj dfSHI GdOjhf(B.s
Keywords: (3GdHMhKs; (3GdeMGSHIs; (3WQb GdHMKs